2017
DOI: 10.18632/oncotarget.15386
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids have a protective effect against lung cancer in female patients with chronic obstructive pulmonary disease: a nationwide population-based cohort study

Abstract: Whether the use of inhaled corticosteroids (ICS) protects patients with chronic obstructive pulmonary disease (COPD) from lung cancer remains undetermined. In this retrospective nationwide population-based cohort study, we extracted data of 13,686 female COPD patients (ICS users, n = 1,290, ICS non-users, n = 12,396) diagnosed between 1997 and 2009 from the Taiwan's National Health Insurance database. These patients were followed-up until 2011, and lung cancer incidence was determined. Cox regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 62 publications
0
32
0
Order By: Relevance
“…In that study, ICS exposure was associated with a trend in favour of diminished cancer mortality. The beneficial effect appears to be dose-dependent, and perhaps more noticeable in women and former smokers [10,15]. It has also been reported in asthmatic patients [16].…”
mentioning
confidence: 79%
“…In that study, ICS exposure was associated with a trend in favour of diminished cancer mortality. The beneficial effect appears to be dose-dependent, and perhaps more noticeable in women and former smokers [10,15]. It has also been reported in asthmatic patients [16].…”
mentioning
confidence: 79%
“…Similarly, Liu et al, report the ICSs (e.g. > 0.0395 gram) have the impact on attenuation of the chronic system inflammation in the COPD support this finding [ 53 ].…”
Section: Discussionmentioning
confidence: 73%
“…A recent study suggested that ICS has a potential role in lung cancer prevention among female COPD patients in Taiwan. 11 However, there are a few limitations of these previous studies, including a relatively short follow-up period. 8,10 In the year of inhaler initiation.…”
Section: Discussionmentioning
confidence: 96%